Full virtual autopsy in a case of a suicidal transthoracic gunshot injury. (June 2020) - Heimer, J.; Gascho, D.; Odermatt, R.; Zoelch, N.; Kottner, S.; Thali, M.J.; Chatzaraki, V.
Highlights: In this case of a transthoracic gunshot injury, all indicated non- and minimally invasive imaging methods were applied. Postmortem computed tomography in combination with angiography allowed for the localization of the wound channel. Postmortem magnetic resonance imaging did not provide relevant additional value for the forensic reconstruction in this case. Postmortem magnetic resonance spectroscopy showed the presence of ethanol in white matter tissue and in cerebrospinal fluid. Abstract: In a case of a single penetrating gunshot injury to the chest, all of the available imaging and imaging-related methods that are routinely used and indicated for reconstructive purposes were applied. These methods included postmortem computed tomography (PMCT), PMCT-angiography, PMCT with postmortem ventilation, postmortem magnetic resonance imaging (PMMR), PMMR-angiography, postmortem magnetic resonance spectroscopy, and three-dimensional surface documentation. This report offers a broad spectrum of imaging data of the same case; therefore, this report constitutes a case-based overview of contemporary postmortem imaging.